(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article explores how teamwork and individualized student development contribute to enhancing educational effectiveness within the Japanese education system. Drawing on recent studies on lesson study, collaborative learning, and individualized approaches, the paper argues that Japan’s unique blend of collective teacher collaboration and personalized learning strategies provides a model for balancing group-based and individual-centered education. The article synthesizes research findings to present an integrated perspective on how Japan maintains a high-performing and adaptable education system.